Effect of urinary tract infection on the risk of prosthetic joint infection: A systematic review and meta-analysis. Issue 3 (June 2021) - Wang, Chenglong; Huang, Wenwen; Gu, Yingdan; Xiong, Jian; Ye, Zhuomiao; Yin, Dong; Mu, Xiaoping
Abstract: Purpose: Urinary tract infection (UTI) are very common in the general population, however it is unclear whether UTI is a risk factor of prosthetic joint infection (PJI). Our purposes were: (1) To determine whether UTI is a risk factor of PJI after joint replacement, and (2) to determine whether the microorganisms causing PJI and UTI are the same. Methods: PubMed, Web of Science, the Cochrane Library, and EMBASE were searched systematically for studies. The effect sizes of RR were calculated for included studies that reported raw counts with 95% CIs. The aim 1 of the study is a meta-analysis; the aim 2 is a systematic review. Results: The aim 1 indicated that the risk of PJI was significantly higher in the UTI group than in the control group (RR = 3.17; 95% CI, 2.19–4.59). The aim 2 indicated that the microorganisms of UTI and PJI were the same in the same patient, and these included Enterococcus faecalis, and Pseudomonas, which supports the theory of PJI occurring via the haematogenous route from the genitourinary tract that harbours bacteria in UTI. Conclusion: This study identified UTI as being significantly associated with PJI after joint arthroplasty and PJI occurring via the haematogenous route from the genitourinary tract harbouring bacteria in UTI. Therefore, postponing surgery and even treating patients with known UTI preoperatively are recommended. Highlights: Urinary tract infection (UTI) as being significantly associated with prosthetic joint infection (PJI). Postponing surgery and even treating patients with UTI. The systematic review supports the theory of PJI occurring via the haematogenous route from UTI.